Quantitative methods for MRI-microscopy comparisons - Kor, DZL (2023)
Magnetic resonance imaging (MRI) is a powerful tool for the in-vivo diagnosis and assessment of neurodegenerative disorders. While numerous MRI techniques have yielded parameters sensitive to microstructural changes in the brain, MRI parameters are infamously non-specific. Different changes in brain tissue structure may result in the same change in MRI signal, making it challenging to pinpoint the exact source of these signal changes.